2020
DOI: 10.1111/jog.14442
|View full text |Cite
|
Sign up to set email alerts
|

Impact of obesity on surgical and oncologic outcomes in patients with endometrial cancer treated with a robotic approach

Abstract: AimThe surgical treatment of endometrial cancer (EC) can be more complicated in obese patients. Robotic surgery could simplify the surgical approach in these patients. The aim of our study was to compare the outcomes of robotic surgery in obese (body mass index ≥30 kg/m2) and nonobese patients.MethodsWe performed a retrospective study on patients with EC benefitting from a robotic approach in our institution. The primary outcome was the 5‐year overall survival (OS). We also assessed the 5‐year recurrence‐free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Briefly, study populations were predominantly white, over 60 years of age, diagnosed with Type I endometrial cancer and had FIGO stage I. Most of studies were conducted in Europe ( n = 20) 12,13,15,18,21,22,27,43–55 and North America ( n = 18) 19,20,23–26,56–67 . The remaining studies were conducted in Asia ( n = 4), 14,68–70 Oceania ( n = 2), 17,71 and South America ( n = 1) 72 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, study populations were predominantly white, over 60 years of age, diagnosed with Type I endometrial cancer and had FIGO stage I. Most of studies were conducted in Europe ( n = 20) 12,13,15,18,21,22,27,43–55 and North America ( n = 18) 19,20,23–26,56–67 . The remaining studies were conducted in Asia ( n = 4), 14,68–70 Oceania ( n = 2), 17,71 and South America ( n = 1) 72 .…”
Section: Resultsmentioning
confidence: 99%
“…The main reasons that studies were rated as low quality ( n = 13) were inappropriate ascertainment of exposure, insufficient follow‐up time, and lack of adjustments for additional variables (Table S3). Additionally, one study reported a point estimate outside the 95% CI and therefore was not included in meta‐analyses 54 …”
Section: Resultsmentioning
confidence: 99%
“…Even though the patients have early-stage cancer, they may not be able to be operated on due to concomitant systemic diseases such as cardiovascular and diabetes mellitus, and they may have to undergo primary radiotherapy. Robotic surgery may provide an advantage over conventional laparoscopy in such patients [68,69].…”
Section: Author Detailsmentioning
confidence: 99%
“…We demonstrated that patients with a BMI ≥ 40 kg/m 2 had a marked increase in P means and P peaks compared with patients with a BMI < 40 kg/m 2 . Some reports state that the incidence of complications does not differ significantly between patients with and without obesity undergoing robotic surgery ( Kawai et al, 2021 ), and some suggest that the effect of a higher BMI on breathing during anesthesia is more significant than the effect of a lower head position ( Sprung et al, 2002 , Suh et al, 2010 ). In the present study, under PCV, a 5° difference in head-down tilt did not significantly affect respiratory status other than the P peak.…”
Section: Discussionmentioning
confidence: 99%